Predestinasi menurut John Calvin - Agustina Pasang (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2019)
Abstract: Calvin was not the first and only person who have preceded the doctrine of predestination, because in his writings he used much of Augustine’s argument to explain the problem of predestination. If predestination is often identified with Calvin it is because he provides a more comprehensive and complete explanation of this doctrine. Predestination is totally God’s deed that by His omniscience, He choose some people to be saved, not because of their good deeds. It talks about God’s ultimate decree about the salvation. In other word, predestination is God’s eternal deed, that by His sovereignty choosing some people to get the grace of salvation, by not counting their merits nor good deeds and some people had been decided to be punished because of their sins.